Model of fulfilling basic needs for the elderly at home based on Balinese culture - I Ketut Suardana; I Wayan Surasta; Made Liandana; I Made Mertha; Ni Luh Putu Sri Erawati (KHD-Production, 2025)
The problems that exist in society related to the elderly are mainly in meeting basic needs, and there is a tendency to get depression. Decreased body function in the elderly can affect physical, mental, and psychosocial changes. This study aims to identify patterns of improvement in the basic needs of the elderly and identify models of basic needs services for the elderly. This research uses a qualitative design where researchers conduct FGDs with in-depth interviews. The sample was taken by purposive random sampling with a sample of 35 people who were divided into six groups. The results of the study showed a discussion rate of 29% for the topic of life support, psychological counseling at 26%, services provided by the family at 18%, care and daily life at 17%, and attitudes of the elderly at 3%. The elderly's life support for walking or toilets is 44%. Tools for asking for help is 31%. The most discussed psychological problem is the exceptional attention level of 77%. The desired service is for families to pay attention to the elderly, which is 38%. Most eating and drinking services are daily care related to defecation assistance (24%), and the attitude of the elderly when they need help is to convey it to trusted people (23%). The importance of integrating comprehensive care models that prioritize the physical, emotional, and social needs of the elderly. By fostering collaboration among families, caregivers, and healthcare professionals, it is possible to create a supportive ecosystem that empowers elderly individuals to lead fulfilling lives.